An analysis of the theory- and employment-demands on mathematics for electrical engineering programmes at technikons - Swanepoel, Jonathan E (School of Education, 2017)
A preliminary study indicated a degree of dissatisfaction with the present mathematics curriculum at technikons amongst academic staff members of technikons as well as members of the electrical-engineering industry. The hypothesis of this study is that the present mathematics curricula for electrical-engineering at technikons are not fully compatible with the demands emanating from the theoretical and the industrial-training (in-service or workplace) components of the training of electrical-engineering technicians. The intent of this study is, firstly, to propose a framework of thought supporting engineering-mathematics curriculum-change in the context of electrical-engineering programmes as offered at technikons. The actual formulation of the syllabus content is supported by a curriculum-change model which takes cognisance of both the theoretical-demands and the workplace- demands in accordance with the aims of co-operative education espoused by technikons in South Africa. Secondly, a literature study of relevant past research leads to the development of a research methodology sympathetic to the present philosophy of technikon education for engineering-technicians in the country. The research methodology involves, firstly, a questionnaire response from practising engineers and technicians. Secondly, it involves the gathering of suggestions from technikon academic staff and the analysis thereof by a work-group representative of all technikons, and led by the researcher. Thirdly, seventy-nine (79) reference-texts to the electrical-engineering programmes (study-levels 1 to 4), offered at the Peninsula Technikon, were analysed for its mathematical content. The research findings supports the hypothesis. The thesis culminates in set of recommendations with regard to the applicability and composition of mathematics syllabi for electrical-engineering programmes at technikons.